Indocyanine green fluorescence improves safety in laparoscopic cholecystectomy using the Fundus First technique: a retrospective study - Haverinen, Susanna; Pajus, Evelina; Sandblom, Gabriel; Cengiz, Yücel (Frontiers in Surgery, 2025)
IntroductionAs one of the most commonly performed surgeries in the world, safety during laparoscopic cholecystectomy (LC) is of utmost importance. Indocyanine green (ICG) has been used for different medical purposes including assessment of liver function since the 1950s. Its use during LC was first described in 2009 by Ishizawa. Since ICG is excreted in the bile, its fluorescent properties can be used to illuminate the bile ducts, and may reduce the risk for bile duct injury and other complications. Previous studies have compared ICG with conventional visualization showing shorter operation time and lower conversion rates during LC performed with traditional operation techniques. Results from LC performed with the Fundus First method (FF-LC) and ICG fluorescence has not been previously reported. The aim of this retrospective study was to compare LC with and without the aid of ICG fluorescence at a Swedish hospital routinely performing FF-LC.MethodsData from all patients operated with LC at Sundsvall General Hospital before and after the implementation of routine ICG between 2016 and 2023 were analyzed.ResultsThe study included 2,009 patients; 1,455 operated with ICG (ICG-group) and 549 without (comparison group). FF-LC was used in 94.9% of all operations. The groups were comparable regarding gender, BMI, age, presence of acute cholecystitis and proportion urgent/elective surgery. ICG was found to be safe, with similar 30-day complication rates between study groups. A lower conversion rate was seen in the ICG-group (1.2% vs. 3.3%, p = 0.001) and there was a non-significant reduction in readmissions (p = 0.054). In univariate analysis, ICG was associated with prolonged operation time, but this was not supported in multivariate analysis. Time to cholangiography was prolonged in the ICG-group in both univariate and multivariate analyses.DiscussionICG fluorescence is an adjunct that could improve the operative safety. Implementation of routine ICG fluorescence at this Swedish hospital was found to be safe and efficient, suggesting improvement in safety during FF-LC. Further studies are needed to see if ICG increases safety in LC.